Individual factors contributing to HIV related stigma among HIV positive youths aged 15-24 years attending the ART clinic at TASO Uganda, Entebbe, Wakiso District. A cross-sectional study. - Kemigisha, Brenda; Masete, George; Nansereko, Hasifa; Naggulu, Immaculate; Nalubega, Jane Frank (Student's Journal of Health Research Africa, 2026)
Background The study aims to identify the individual factors contributing to HIV related stigma among HIV positive youths aged 15-24 years attending the ART clinic at TASO Uganda, Entebbe, Wakiso District. Methods A descriptive cross-sectional study design employing a quantitative research method was used to collect data among HIV positive youths aged 15-24 years from a sample of 92 participants who were sampled using a consecutive sampling method. Data was collected with a structured questionnaire, coded, analysed using Microsoft Excel (2013) programs, and presented in frequency tables, graphs, and pie charts. Results Nearly half 40, 43.5%) of the respondents were aged between 25 and 30 years. The majority, 36 (39.1%) of the respondents reported that when stressed about their HIV status, they tend to blame themselves or someone else, while 30 (32.6%) preferred to keep to themselves. Most 48 (52.2%) of the respondents believed that HIV drugs help youths live a long and healthy life, whereas 34 (37%) said the drugs protect them from infections. A large proportion, 62 (67.4%) of the respondents had experienced emotional violence such as insults or humiliation after discovering their HIV status, while 15 (16.3%) had suffered physical violence and 10 (10.9%) sexual violence. Nearly half 40, 43.5%) of the respondents reported that they had not disclosed their HIV status to anyone, while 34 (37%) had disclosed to their parents or guardians. Conclusion Individual factors such as fear of disclosure, low self-esteem, and internalised stigma reduced confidence and social interaction. Recommendations Health authorities should conduct continuous anti-stigma campaigns through schools, religious institutions, and community gatherings to promote acceptance and correct misconceptions about HIV.